Ответ:
Пошаговое объяснение:
1/4(2а-4)-1/3(5b+6) а=2 1/2; b=3/15
1/4(2а-4)-1/3(5b+6) = 1/2а - 1 - 5/3b -2= 1/2а - 5/3b -3
1/2а - 5/3b -3 = 1/2 * 2 1/2 - 5/3 * 3/15 -3= 1/2 * 5/2 - 1/3 - 3= 5/4 - 1/3 - 3=
15/12 - 4/12 - 3= 11/12 -3= -2 1/12
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1/4(2а-4)-1/3(5b+6) а=2 1/2; b=3/15
1/4(2а-4)-1/3(5b+6) = 1/2а - 1 - 5/3b -2= 1/2а - 5/3b -3
1/2а - 5/3b -3 = 1/2 * 2 1/2 - 5/3 * 3/15 -3= 1/2 * 5/2 - 1/3 - 3= 5/4 - 1/3 - 3=
15/12 - 4/12 - 3= 11/12 -3= -2 1/12